Building consumer cultural capital in the premium wine domain in China through tourism - Ferguson, Graham; Cheah, Isaac; Lee, S. (Routledge, 2018)
Getting novice consumers of premium wine, in new markets, to consider brands outside of the most recognised, dominant wine regions is a challenge for premium wine marketers. This is particularly the case for premium Australian wine brands competing in the China market where French wines dominate (Cohen et al., 2017; Lee et al., 2015; Wu, 2017). The China market represents a tantalising opportunity for Australian premium wine exporters (Cohen et al., 2017; Cohen, Corsi & Lockshin, 2015; Maguire and Lim, 2015) because of market potential but the challenge of being accepted by novice wine consumers may dissuade some brands from entering when they can enter much more advanced wine markets in Europe or the USA (Galbraith and Gao, 2016).